Effects of methimepip and JNJ-5207852 in Wistar rats exposed to an open-field with and without object and in Balb/c mice exposed to a radial-arm maze - Ennaceur, Abdel; ABUHAMDAH, Rushdie M.; Lethbridge, Natasha L.; Chazot, Paul L.; van Rensburg, Ruan (Frontiers in Systems Neuroscience, 2012)
The role of the histamine H3 receptor in anxiety is controversial, due to limitations in drug selectivity and limited validity of behavioral tests in previous studies. When exposed to an empty open field, Wistar rats spent more time in the outer area and made very low number of brief crossings in the central area. However, when an object occupied the central area, rats crossed frequently into and spent a long time in the central area. Administration of a range of different doses of methimepip (H3 receptor agonist) reduced the entries into the central area with a novel object, indicating enhanced avoidance response. When balb/c mice were exposed to an open space 3D maze, neither methimepip nor JNJ-5207852 (H3 receptor antagonist/inverse agonist) induced entry into the arms of the apparatus, indicative of lack of anxiolytic effects.